Bakelicous: an online booking for pretty small bakery / Siti Sarah Halim - Halim, Siti Sarah (2016)
This project is about developing Bakelicious: An Online Booking for Pretty Small Bakery. The owner of Pretty Small Bakery, Mrs. Hamiza Hamid, faced the problem in keeping track of the customer ordering. Currently, she is using manual order which is the customer needs to call or messaging her through application WhatsApp to ask the details of the order. Then, she needs to send the details through application WhatsApp to the customers. The purpose of this project is to develop Bakelicious: An Online Booking for Pretty Small Bakery. The methodology used in this development of this project is Waterfall model of System Development Life Cycle (SDLC) approach and the reason why this project decided for this methodology is because it is simple and easy to use. In this context, the customer can register, login into the system, search the products, make an order, update their information and logout from the system while the admin which is the owner of Pretty Small Bakery itself can login into the system, manage the events, manage the order, add new staff, update customers information, generate the reports for the performance of business purpose, and logout from the system. Meanwhile, the staff also can do the same thing with the admin except generate the reports. The project will bring benefit to both the customers and the shop itself. Last but not least, Bakelicious: An Online Booking for Pretty Small Bakery could be benefit to the Pretty Small Bakery in order to promote their products.